Sandymancer - Edison, David (Tor, Tor Publishing Group, 2023)
"All Caralee Vinnet has ever known is dust. Her whole world is made up of the stuff; water is the most precious thing in the cosmos. A privileged few control what elements remain. But the world was not always a dust bowl and the green is not all lost. Caralee has a secret--she has magic in her bones and can draw up power from the sand beneath her feet to do her bidding. But when she does she winds up summoning a monster: the former god-king who broke the world 800 years ago and has stolen the body of her best friend. Caralee will risk the whole world to take back what she's lost. If her new companion doesn't kill her first"--